KONSEP PEMBENTUKAN INDIVIDU DALAM PENDIDIKAN ISLAM DAN RELEVANSINYA DI ERA DIGITAL - Mohamad Shabirin Shaddiq; Kholili Hasib (Nusantara Hasana Journal, 2026)
This study aims to analyze the concept of individual formation in Islamic education and its relevance in the digital era. The research is motivated by increasing moral and ethical issues among students due to the rapid development of digital technology, social media, and artificial intelligence. This study employs a qualitative approach using library research. Data were collected from relevant literature and analyzed using descriptive-qualitative techniques through data reduction, presentation, and interpretation. The findings show that individual formation is the core of Islamic education, aiming to develop human potential in intellectual, spiritual, moral, and social dimensions. This concept is integrated through four main frameworks: fitrah, ta’dib, akhlaq, and insan kamil. These elements form a holistic educational foundation that remains relevant in addressing digital era challenges through Islamic digital literacy based on moral awareness, responsibility, and proper conduct in technology use.